DIGITAL ADMINISTRATIVE SERVICES TO IMPROVE THE PERFORMANCE OF ADMINISTRATIVE SERVICES AT THE PALU IMMIGRATION OFFICE - Isidorus Anung Prabadhi; Aqil Nayottama Ardraputra L. (Jurnal Abdimas Imigrasi, 2022)
This research is about the effectiveness of using the Immigration Management Information System by the Class 1 Immigration Office in Palu in realizing the Immigration Trifunction. In this study, the reasons and factors underlying how to use SIMKIM at the Immigration Office Class 1 Palu in carrying out immigration duties and functions at the Immigration Office Class 1 Palu are analyzed. This study used the Forum Group Discussion (FGD) method, demonstrations, and evaluations in implementing the use of SIMKIM in the field. By analyzing the use of SIMKIM at TPI Soekarno Hatta, it is hoped that we can find out how the process was carried out, the obstacles and problems encountered. From the results of data processing from the results of the Forum Group Discussion (FGD), demonstrations, and evaluations, it can be concluded that the use of SIMKIM in the field seen from the immigration service function has been going quite well even though obstacles and problems often arise that cannot be resolved immediately so there is a need to improve quality HR, update hardware and software and harmonize policies with Standard Operating Procedures as well as software and hardware